SPORT IN SCHOOLS: AN ANALYSIS OF MEANS MORE SPORTS PERFORMED BETWEEN STUDENTS OF ELEMENTARY EDUCATION II EDUCATIONAL CENTER OF APPLIED RESEARCH - CEPA (Fiep Bulletin - online, 2014)
The presence of sports activities in physical education classes is a reality that grows annually. After the choice of Brazil as a country cedes World Cup and Olympics this reality grew even more. Motivated by previous research on sport as a hegemonic practice in physical education classes, woke up the curiosity to find out how this actually happens in public schools in Maceió. This study deals with an investigation of the practice of sport within physical education classes, which sports and what greater acceptance criterion used in choosing this sport for physical education teachers in the school? It was also the object of research, the importance of sport in physical education classes and if it happens a hegemony of any sport in public schools . The research aimed to analyze how is teaching in physical education classes, identify which modalities are most present in the school. To achieve our objectives, we conducted a field survey in which data were collected through questionnaires, aimed at teachers of Physical Education of School of Seven State Schools Educational Complex CEPA located in Maceio, State of Alagoas. The results were obtained as with the content analysis technique. It was found that the majority of teachers consider the sport as an activity area for socialization and education of students, and under educated still have a sport, futsal, being taught so hegemonic.
Keywords: Physical Education; Sport; School.